أثر تشكيلة المحكمة الدستورية على أدائها الدستوري في الجزائر والمغرب - دراسة مقارنة - تريعة, نوارة; شبري, عزيزة (جامعة الوادي university of eloued, 2022)
حرص المشرع الدستوري في دولتي الجزائر والمغرب على وضع مجموعة من الضوابط التي تحكم تشكيلة المحكمة الدستورية، بما يستجيب بنوعية وطبيعة المهام الموكلة إليها بموجب أحكام الدستور، ويضمن في نفس الوقت استقلالها عن كل السلطات. إن حياد المحكمة الدستورية وتجردها وموضوعيتها يلعب دورا كبيرا في سلامة آرائها وقراراتها ويرفع من مستوى أدائها في مجال الرقابة الدستورية. The constitutional legislator in the countries of Algeria and Morocco was keen to put a set of controls that govern the formation of the Constitutional Court, in a manner that responds to the quality and nature of the tasks entrusted to it under the provisions of the Constitution, and at the same time ensures its independence from all authorities. The impartiality, impartiality and objectivity of the Constitutional Court plays a major role in the integrity of its opinions and decisions and raises the level of its performance in the field of constitutional oversight
مقال
Keywords: المحكمة الدستورية، الرقابة الدستورية، رئيس الجمهورية، الملك،الحصانة، أداء اليمين; Constitutional Court; constitutional oversight; president of the republic; king; immunity; swearing in